2009
DOI: 10.1007/s11244-009-9415-x
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Mesoporous Aluminosilicates Assembled from Dissolved LTA Precursors

Abstract: Aluminosilicate sols containing Si-O-Al bonds were obtained by dissolving zeolite LTA crystals in HCl solution. The solutions were used as single-source molecular precursors of silicon and aluminum. Highly ordered cage-like mesoporous aluminosilicates with Si/Al ratios ranging from 13 to 35 were synthesized using PEO 106 P-PO 70 PEO 106 triblock copolymer aqueous solution and LTA dissolved in HCl solution under mild acidic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…They indicated that the random and selective removal of aluminum from the LTA structure results in the release of silicon followed by complete crystal disintegration. In our previous study, the LTA-dissolved HCl solution contains entirely distinct aluminum and silicon precursors [9][10][11]. Thus, the pure silica mesoporous particles were obtained from LTA-dissolved in HCl solution of more than 3.0 M. The LTA-dissolved HCl solution contains entirely distinct Al and Si species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They indicated that the random and selective removal of aluminum from the LTA structure results in the release of silicon followed by complete crystal disintegration. In our previous study, the LTA-dissolved HCl solution contains entirely distinct aluminum and silicon precursors [9][10][11]. Thus, the pure silica mesoporous particles were obtained from LTA-dissolved in HCl solution of more than 3.0 M. The LTA-dissolved HCl solution contains entirely distinct Al and Si species.…”
Section: Resultsmentioning
confidence: 99%
“…Al atoms were fixed in the zeolite nanoblocks and directly introduced into the mesostructure along with the nanoblocks. With HCl the only acid source, the particles possess the body-centered cubic Im3m symmetry [9][10][11]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable effort was invested in developing mesoporous titania and titania-silica catalysts since the early works of Corma et al and Tanev et al The goal is to develop more active catalysts that are stable under severe reaction conditions. , Various approaches including preparing mesoporous catalysts with thick pore walls and incorporating zeolitic structures had been reported. Mesoporous catalysts with excellent activity and good hydrothermal stability had been synthesized from mixtures containing zeolite nanoparticles. It is believed that the zeolite nanocrystals either dissolved during the synthesis into zeolitic fragments that are then incorporated into the pore wall or actively nucleate primary and secondary zeolite building units that are inserted into the wall structure. This work attempts to clarify the role of the zeolite seeds in the synthesis of the mesoporous titania-silica catalysts.…”
Section: Introductionmentioning
confidence: 99%